An interesting observation of Eurasian beaver Castor fiber Linnaeus, 1758 in Vidovec Cave (Metlika, Slovenia) - Tinkara Kepic; Meta Valenčič; Marisa Schlamberger; Tjaša Trajbarič; Łukasz Popowicz; Annasibila Požrl; Valentina Jakob; Klara Žos; Ester Premate (Natura Sloveniae)
The Eurasian beaver is a common rodent which became extinct in Slovenia in the 18th century and reappeared in the 1990’s. This field note describes an encounter with a beaver inside the Vidovec Cave (Metlika, Southeastern Slovenia). Apart from a sign of beaver presence, we also noticed a straw mat presumably used for sleeping. The described observation is probably the first of its kind in Slovenia, although similar observations are known from Croatia as well.